Jezična akomodacija na Twitteru - Ljubešić, Nikola (Slavistična revija, 2019)
In this paper we investigate the phenomenon of linguistic accommodation among Serbian Twitter users by analysing geo-encoded Twitter messages published between 2013 and 2016 in the area of Bosnia, Croatia, Montenegro and Serbia. We describe the linguistic production of Twitter users via 16 variables that are known to vary among the speakers of the pluricentric BCMS language. We compare that production of mobile Serbian Twitter users to that of non-mobile Serbian Twitter users, and by comparing the mobile users' language production inside and outside Serbia. While the first analysis shows support for accommodation, the second analysis yields no signal for that phenomenon.
Keywords: BCHS; družbena omrežja; geo-encoded messages; geokodirana sporočila; Serbian; social media; srbščina; Twitter